2004
DOI: 10.1007/s11745-004-1195-5
|View full text |Cite
|
Sign up to set email alerts
|

Trans, saturated, and unsaturated fat in foods in the united states prior to mandatory trans‐fat labeling

Abstract: On July 11, 2003, the U.S. Food and Drug Administration published a final rule amending its food-labeling regulations to require that trans FA be declared in the nutrition label of conventional foods and dietary supplements. The effective date of this final rule is January 1, 2006. This places some urgency on increasing the number and types of currently available foods for which there are trans-fat data. Compositional databases on trans fat content of food are currently limited. The purpose of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 4 publications
2
46
0
2
Order By: Relevance
“…In most databases, there would not be a data line for each brand of food, at best there may be a few brand-specific lines and a composite of different brands. A similar variability was reported by Satchithanandam et al (2004), who found that the TF content of tortilla and potato chips in the Washington DC, USA area varied from 0 to 17 g per 100 g chips.…”
Section: Per Capita Food Consumptionsupporting
confidence: 84%
“…In most databases, there would not be a data line for each brand of food, at best there may be a few brand-specific lines and a composite of different brands. A similar variability was reported by Satchithanandam et al (2004), who found that the TF content of tortilla and potato chips in the Washington DC, USA area varied from 0 to 17 g per 100 g chips.…”
Section: Per Capita Food Consumptionsupporting
confidence: 84%
“…For example, a review of 37 different kinds of bread, cake, and related products in the Washington, DC, area showed that the average grams of trans fatty acids (grams per 100 g fat) ranged from 0.0 to 48.8. 19 The significant difference in the trans fatty acid content in products within each food category is due to differences in the type of fats and oils used in the manufacturing process. …”
mentioning
confidence: 99%
“…Selain margarin dan fast food, hasil penelitian U.S. Food and Drug Administration pada tahun 2003 menyebutkan bahwa produk makanan seperti roti, kue, kerupuk, kentang beku, snack asin, minyak sayur yang mengandung shortening, mayones, dan sereal sarapan kering juga merupakan jenis pangan yang mengandung asam lemak trans (Satchithanandam et al 2004).…”
Section: Pendahuluanunclassified